Mechanical, thermal and thermoelectric properties of MX2 (M = Zr, Hf; X = S, Se). (December 2020) - Abdulsalam, Mahmud; Rugut, Elkana; Joubert, D.P.
Abstract: In this paper, we used density functional theory to study the mechanical and thermal properties of MX2 (M = Zr, Hf; X = S, Se) in P21 /m structure. Results from elastic constants and phonon band structure indicated that the structures were found to be stable against mechanical distortions. These MX2 are brittle and their dominant bonding type is ionic in nature based on our computed mechanical properties. Thermal properties show that the specific heat capacity at constant volume of the selenides is greater than that of the sulphides of hafnium and zirconium. Additionally, we computed the lattice thermal conductivity as well as the transport coefficients with respect to temperature over a range of charge carrier concentrations, ranging from the Seebeck coefficient, electrical conductivity, electronic contribution to total thermal conductivity and consequently fuse them so as to calculate their respective power factors as well as the dimensionless figure of merit of the hafnium and zirconium dichalcogenides considered hereby.